(untitled) (Materiali di Estetica. Terza serie, 2024)
The article offers an exploration of the author’s intellectual exchanges with Fulvio Papi, illustrating how Papi’s philosophical insights profoundly influenced his own work. Sarcinelli describes their discussions as intellectually enriching, spanning a wide range of topics from political theory to personal anecdotes. He highlights Papi’s role in shaping critical and philosophical discourse through his ability to clarify complex ideas and contribute to ongoing debates about the role of philosophy in understanding and critiquing contemporary society. The article also touches on Papi’s academic contributions, particularly his reinterpretations of Marx’s theories, showing his continued relevance in the analysis of modern socio-economic conditions.